IMPLEMENTATION OF STEAM IN PLAY ACTIVITIES ON THE DEVELOPMENT STUDENTS IN THE PRE-OPERATIONAL STAGE - 'Afifah, Azka; Febrilia, Yeyen; Sataroh, Sindy; Tahara Arisandi, Ulyma (As-Sulthan Journal of Education, 2026)
The purpose of this qualitative study is to describe the implementation of STEAM education through play-based activities, especially making a fan from origami paper in the pre-operational stage. This study not only focus in outcomes but also in the learning process. This study showed the integration of each elements in STEAM based on play activity. The subject of this study are students in Grade 1 from one of the national school in Pangkalpinang who is in pre-operational stage. The data collected by observation, interview, and documentation. The researchers are in the class to observe the implementation. The interview conducted to students during the class. The documentation are the photos and videos of learning process. The data analyzed using Miles & Huberman Model such as data reduction, data display, conclusion. The results showed that implementation of STEAM through origami paper effectively bridges the gap between abstract mathematical concepts and concrete play. This study concludes that play-based STEAM implementation is effevtive in stimulating the cognitive and sensory motor of pre-operational stage.